1987
DOI: 10.1055/s-2008-1026781
|View full text |Cite
|
Sign up to set email alerts
|

Die Corticosteroid-abhängige Dezimierung der Leukämiezellzahl im Blut als Prognosefaktor bei der akuten lymphoblastischen Leukämie im Kindesalter (Therapiestudie ALL-BFM 83)

Abstract: In therapy study ALL-BFM 83 a total of 630 patients with acute lymphoblastic leukemia (ALL) have prospectively been evaluated for initial response on therapy with corticosteroids. It was the aim to qualify the in vivo cytoreduction as a new predictor for therapy failure. All patients were exposed for 7 days to prednisone before combination chemotherapy at day 8 has been started. At day 0 one additional dose of Methotrexate was given intrathecally. Therapy for all patients with non-B-ALL has been stratified acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(68 citation statements)
references
References 23 publications
0
67
0
1
Order By: Relevance
“…The in vivo prednisone response as used in the BFM studies has been found to be one of the strongest prognostic factors for therapy outcome in childhood ALL (1,29,33). The in vitro prednisolone sensitivity of untreated leukemic cells, as determined by the MTT assay, is a strong risk factor for outcome as well and can predict the occurrence of a relapse even within the group of patients with a good in vivo prednisone response (2,4,5,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vivo prednisone response as used in the BFM studies has been found to be one of the strongest prognostic factors for therapy outcome in childhood ALL (1,29,33). The in vitro prednisolone sensitivity of untreated leukemic cells, as determined by the MTT assay, is a strong risk factor for outcome as well and can predict the occurrence of a relapse even within the group of patients with a good in vivo prednisone response (2,4,5,31).…”
Section: Discussionmentioning
confidence: 99%
“…These protocols start with a 7-day monotherapy of prednisone and one intrathecal dose of methotrexate. The prednisone response was determined on day 8: prednisone good response is defined as <1,000 leukemic blasts/AL peripheral blood and prednisone poor response as z1,000 blasts/AL (29). Patient material was taken before initial therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Details regarding dosage and exact timing are provided in the key references published earlier [13][14][15]17,21 and are provided in Supplementary Tables 1-5. The major study questions addressed in each trial are summarized under section Introduction.…”
Section: Treatmentmentioning
confidence: 99%
“…The number of leukemic blasts in PB was centrally evaluated. 14 Extensive data analysis revealed that in approximately 10% of the patients a leukemic blast cell count in PB of 1000 per ml or more on day 8 ('Prednisone poor response', PPR) could be found. This is highly predictive of a particularly high relapse risk.…”
Section: Introductionmentioning
confidence: 99%
“…From October 1983 to September 1986, 709 previously untreated children with ALL were stratified for risk-adapted multidrug chemotherapy in the ALL-BFM 83 multicenter trial [11]. Complete immunophenotypic determinations were performed in 607 (85.6%) of these patients.…”
Section: Patientsmentioning
confidence: 99%